A multi-institutional assessment of changes in higher education teaching and learning in the face of COVID-19. Issue 3 (16th April 2022) - Bartolic, Silvia K.; Boud, David; Agapito, Jenilyn; Verpoorten, Dominique; Williams, Siobhan; Lutze-Mann, Louise; Matzat, Uwe; Moreno, Ma Monica; Polly, Patsie; Tai, Joanna; Marsh, Heidi L.; Lin, Lin; et al.
ABSTRACT: COVID-19 has had a profound influence on the conduct of teaching and learning in higher education. Almost everywhere a sudden shift occurred as educators transitioned courses from mainly face-to-face teaching and learning to emergency remote instruction, mostly conducted online. While details varied for individual faculty members, institutions, and countries, all confronted new challenges. We examine the immediate effects of COVID-19 on teaching and learning in higher education. Our results are based on a sample of 309 courses, and the academic staff who taught them, at eight colleges and universities varying in size and context across four continents. We document first how institutions, and their instructors, varied in their capacity for dealing with the rapidity of the COVID-19 teaching and learning pivot. We further demonstrate that the suddenness of the pandemic's onset, and the quick response this demanded of instructors, meant that there was little systematic patterning in how academic staff were able to adapt – save for nimbleness. Rapidity of response meant differences were far more idiosyncratic than they were systematic, at least with respect to how individual faculty responded.